A critical study on limitations of media on democracy of India - RajalakshmiT.N, Mrs. S.P. Vidyassri (International Journal of Advanced Science and Technology, 2020)
Media plays an important role in the democracy of India .They effectively perform in the performance of specific states .It is the media which strengthens the democratic norms and values and also accelerates the pace of development Without mass communication there would not be much development in modern society but there is controversy that freedom of media would be harmful to democracy.The main objective of the study is to know whether people are aware of limitations of media and about the Article 19(1)(a) of Constitution freedom of press and to find out limitations of media is a bane or boon and to spread awareness among people about this topic. The research has followed Empirical research with a convenient sampling method. The sample size covered by the researcher is 251. The result observed from the analysis of the study is that restrictions must be there for the welfare and security of our country.